Evaluation of the selective antibacterial activity of Eucalyptus globulus and Pimenta pseudocaryophyllus essential oils individually and in combination on Enterococcus faecalis and Lactobacillus rhamnosus - Ambrosio C.M.S. (2018)
The authors are grateful to the “Ministerio de Educación del Perú” from the Peruvian government for Carmen M.S Ambrosio M.Sc. scholarship, granted by the program “Programa Nacional de Becas y Crédito Educativo” (PRONABEC). Also, the author thanks CIENCIACTIVA for the recent Carmen M.S. Ambrosio Ph.D. scholarship, from the “Consejo Nacional de Ciencia, Tecnología e Inovación Tecnológica” (CONCYTEC-Peru; Contract 278-2015-FONDECYT).